Isolation of Kaempferia angustifolia rosc., Alpinia conchigera griff. and Curcuma mangga val. and Van zijp. phytochemicals and their bioactivities - Tang, Sook Wah (2011)
Zingiberaceae is one of the most important herbaceous families found in tropical forests. In this research, Kaempferia angustifolia Rosc. (Kunci pepet), Alpinia conchigera Griff. (lengkuas ranting) and Curcuma mangga Val. & Van Zijp. (mango turmeric) were selected for phytochemical and bio-activity studies. Several classes of chemical constituents have been isolated and characterized spectroscopically. This included cyclohexane epoxides, chalcones, terpenes, phenylpropanoids and diarylheptanoids. From Kaempferia angustifolia, crotepoxide (29), boesenboxide (30), 2'-hydroxy-4,4',6'-trimethoxychalcone (31), zeylenol (28), 6-methylzeylenol (32), abiet-8(14)- enepenta-6,7,9,11,13-ol (kaempfolienol) (84), (24S)-24-methyl-lanosta-9(11),25-dien-3β-ol (80), pipoxide (25) were isolated besides β-sitosterol (82) and its glycoside (83). Similarly, β-sitosterol-3-O-β-D-glucopyranoside (83) was also obtained from the rhizomes of Alpinia conchigera along with p hydroxycinnamaldehyde (55), 1’-acetoxychavicol acetate (33) and trans-p-coumaryl diacetate (53). Furthermore, β-sitosterol (82), curcumin (59), demethoxycurcumin (60) and 12,17-epoxy-3β,17-dihydroxylabda-13-en-16,15-olide (curcumangganol)(94) were yielded from the Curcuma mangga extract. The structure of zeylenol (28)was modified by using chemical reactions to give zeylenol diacetate (89), zeylenol triacetate (90) and zeylenol epoxide (91) derivatives. p-Hydroxycinnamaldehyde (55)was also derivatized to p-methoxycinnamaldehyde (92) and pacetoxycinnamaldehyde (93). 5S,6S,7S,9S,10S,11R,13S-Abiet-8(14)-enepenta-6,7,9,11,13-ol (Kaempfolienol) (84)and epimeric 12,17-epoxy-3β,17-dihydroxylabda-13-en-16,15-olide (curcumangganol I and II) (94) were isolated as new compounds. The stereostructure of compound 84 was determined on the basis of its single crystal X-ray crystallography. Compounds 80, 83 and (+)-25 were firstly described from the respective species. Structures of all the isolated phytochemicals and structurallymodified compounds were elucidated by using various spectroscopic methods [infrared (IR), mass spectrometry (MS) and nuclear magnetic resonance (NMR)] and by comparison with the previous literature. Crude extracts, isolated constituents and derivatives were subjected to cytotoxic screening against four cancer cell lines (HL-60, HT-29, MCF-7 and HeLa) as well as antimicrobial testing. Crude extracts of Kaempferia angustifolia were not active in the cytotoxic assays, with IC50 values more than 30 μg/mL. Isolated phytochemicals from this species exhibited different degrees of inhibitions against the cancer cell lines tested, with 2’-hydroxy-4,4’,6’-trimethoxychalcone (31) and (24S)-24-methyl lanosta-9(11),25-dien-3β-ol (80) demonstrating the most prominent cytotoxic activities (IC50 < 8 μg/mL) against certain cell lines. As for Alpinia conchigera, nonpolar and semi-polar extracts showed strong cytotoxic properties against human promyelocytic leukaemia (HL-60), human breast cancer (MCF-7) and human cervical cancer (HeLa) cell lines. 1’-Acetoxychavicol acetate (33) and phydroxycinnamaldehyde (55) displayed a broad spectrum of anticancer effects against the tested cell lines. In addition, the chloroform extract of Curcuma mangga and isolated compounds 59, 60 and 94 also exhibited potent cytotoxic activities in the study. In antimicrobial screening test, extracts and constituents of Kaempferia angustifolia were not active. On the other hand, the crude hexane, chloroform and ethyl acetate extracts of Alpinia conchigera were strongly active against Salmonella choleraesuis in the antimicrobial assay. In antifungal screening test, hexane and ethyl acetate extracts of Alpinia conchigera showed slight inhibition on Saccharomyces cerevisiae. 4- Hydroxycinnamaldehyde (55) showed a remarkable activity in the antimicrobialtesting with a diameter of inhibition zone > 20 mm. The chloroform-soluble fraction of Curcuma mangga and demethoxycurcumin (60) showed negative results in the antimicrobial and antifungal screenings but curcumangganol (94) from the extract demonstrated a moderate inhibitory activity towards Bacillus subtilis (B29).